Correlation between lower limb alignment and patellofemoral pain syndrome among badminton players in UTAR - Hee, ZiYu (2022)
Badminton is a low-risk sport when comparedto other popular sports since most injuries do not require surgical intervention. However, injuries are more common nowadays in modernbadminton such as injury to the lower limbs. There was a lack of studies onbadminton players' lower limb alignment and the prevalence of PFPS. Tofind out regarding the correlation between lower limb alignment andPFPSamong badminton players, a study will be conducted at UTARto studythecorrelation between lower limb alignment and PFPS among badmintonplayers in UTAR Convenience sampling was used and 40 participants (Male=19, Female=21) were successfully recruited. The demographic data, KujalaAnterior Knee Pain Scale (AKPS) was filled up by the participants, whilelower limb alignments (hamstring length, q-angle and navicular droptest) were measured. The data collected was analyzed using Pearson’s CorrelationTest hamstring length for and Spearman’s Correlation Test for q-angleandnavicular drop test using the IBM Statistical Package for Social Sciences(SPSS) software. High prevalence of hamstring tightness and normal readings of q-angle and navicular drop test can be found among badminton players. Prevalence of PFPS according to the Kujala AKPS is low(10.0%). Thecalculated r-values and p-values are as follows, right hamstring length(r=-0.108, p=0.506), left hamstring length (r=-0.171, p=0.292), right q-angle(r=0.015, p=0.925), left q-angle (r=0.040, p=0.807), right navicular drop(r=-0.221, p=0.171), left navicular drop (r=-0.273, p=0.088). All the p-valuesofthe lower limb alignments were more than 0.05, which fails to reject thenull hypothesis. Thus, the result of this research study is there is no significant correlation between lower limb alignment and patellofemoral pain syndrome In conclusion, lower limb alignments (hamstring length, q- angle, navicular drop) had no significant correlation to patellofemoral pain